Contingent Convertibles: Can the Market Handle them? - Gera Kiewiet; Iman van Lelyveld; Sweder van Wijnbergen (Tinbergen Institute, 2017)
The recent financial crisis has led to the introduction of contingent convertible instruments (CoCos) in the capital framework for banks. Although CoCos can provide benefits, such as automatic recapitalization of troubled banks, their inherent risks raise questions about whether they increase the safety of the banking system. We show that concerns about CoCos in just a single bank can result in the decline of an entire market, with investors apparently unable to distinguish safe from risky bonds. In times of market-panic, investors tend to rely on credit ratings instead of estimating the real risks of missing coupon payments. We provide several recommendations to improve the capital requirements regime for banks.
Keywords: G01; G21; G32; 330; Contagion; Contingent Convertible Capital; Systemic Risk